2021
DOI: 10.1021/acs.jchemed.1c00647
|View full text |Cite
|
Sign up to set email alerts
|

Investigating General Chemistry Students’ Ideas of the Role of Scientific Instruments

Abstract: Scientific instruments have long been a vital part of science, paving pathways to remarkable scientific advancements. Such advancements have changed the world both socially and culturally, especially in the past few decades. Students can be introduced to this idea through the concepts of nature of science (NOS): scientific observations are often filtered through apparatus, inferences can be made through observations, and science is a socially and culturally embedded practice. The curriculum often fails to emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Where students understand the theoretical underpinnings of a process, such as spectrophotometry, this impacts their psychomotor and affective learning. This adds to the findings of An and Holme that providing information about instrumentation can improve students’ use of instruments and those of Miller et al that students using instrumentation in the lab preferred to understand it conceptually before learning to use an instrument . Unfortunately, many students do not understand the theory behind spectrophotometry, suggesting the need for more research into why students are not learning the theory even as they express their preference to understand it first.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Where students understand the theoretical underpinnings of a process, such as spectrophotometry, this impacts their psychomotor and affective learning. This adds to the findings of An and Holme that providing information about instrumentation can improve students’ use of instruments and those of Miller et al that students using instrumentation in the lab preferred to understand it conceptually before learning to use an instrument . Unfortunately, many students do not understand the theory behind spectrophotometry, suggesting the need for more research into why students are not learning the theory even as they express their preference to understand it first.…”
Section: Discussionmentioning
confidence: 72%
“…27 As most incoming students' laboratory experience is with balances, glassware, and Bunsen burners, the introduction of an instrument as complex as a spectrophotometer is likely to be met with anxiety and nervousness. 26 This is part of students' overall anxiety with the prospect of laboratory work. 28 Thus, student success in a laboratory that requires collecting and analyzing spectrophotometric data is anything but assured and the ability to link conceptual understanding with technical skill is a difficult prospect.…”
Section: Introductionmentioning
confidence: 99%
“…As a source of inspiring innovations, the safe operations for preventing possible risks during the electrospinning process are related closely to the electrospinning instrument, particularly its core part, namely, the spinneret . Scientific instruments have long been a vital part of science, paving the pathway to remarkable scientific advancements and provoking students’ interest and motivation toward practical learning and innovations . A series of related innovations from the students are exhibited.…”
Section: From Knowing the What-why-how Of Professional Techniques For...mentioning
confidence: 99%
“…A series of related innovations from the students are exhibited. These innovations, which result from the promotion of safety education of the students in the laboratory, include how to implement (1) single-fluid blending electrospinning by using a Teflon-coated metal spinneret, (2) coaxial and triaxial electrospinning using a polymer-metal-combined spinneret, , (3) side-by-side electrospinning through Teflon-coated parallel metal capillaries, and (4) the collection of samples for transmission electron microscopy (TEM) and aligned nanofibers while avoiding high voltage . How these innovations have successfully deepened students’ cognition of electrospinning is also depicted.…”
Section: From Knowing the What-why-how Of Professional Techniques For...mentioning
confidence: 99%
“…Of importance, it has also been reported that students exposed to and able to use advanced instrumentation in their introductory laboratories are more independent, have more developed critical thinking skills, and are more empowered than students who do not have the access. 21,22 In these studies, students seemed to enjoy working with the instruments all while still learning fundamental laboratory techniques.…”
Section: ■ Introductionmentioning
confidence: 99%